Cost-effectiveness of omalizumab in adults with severe asthma: results from the Asthma Policy Model. - Wu, Ann C; Paltiel, A David; Kuntz, Karen M; Weiss, Scott T; Fuhlbrigge, Anne L (The Journal of allergy and clinical immunology, 2007)
Omalizumab (trade name Xolair) is approved by the US Food and Drug Administration for treatment of moderate-to-severe allergic asthma. Given the high acquisition cost of omalizumab, its role and cost-effectiveness in disease management require definition.
Keywords: Anti-Allergic Agents; Antibodies, Anti-Idiotypic; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Asthma; Cost-Benefit Analysis; Humans; Models, Theoretical; Severity of Illness Index